High Suicide Rates among Nepalese Population: Need for Action - Pandey, Achyut Raj; Paudel, Sudip; Belbase, Pradeep (Journal of Nepal Health Research Council, 2022)
Suicide is a global public health problem and the burden has remained stable for last decades. The age standardized suicide rate was 9.77 per 100,000 in 2019 with males and older population being more affected. Based on age, the highest suicide rate was observed in individuals of age 80 years with suicide rate of 64.9 per 100,000 in male, 18.2 per 100,000 in female and 37.4 per 100,000 in both sexes in this age group. In all age group, the suicide rates are higher among males compared to females. Universal, selective and indicative preventive strategies should be implemented to reduce the burden of suicide in Nepal.Keywords: Nepal; prevention; suicide.